How to Implement Digital Clinical Consultations in UK Maternity Care: the ARM@DA Realist Review - Catrin Evans; Georgia Clancy; Kerry Evans; Andrew Booth; Benash Nazmeen; Candice Sunney; Mark Clowes; Nia Wyn Jones; Stephen Timmons; Helen Spiby (Health and Social Care Delivery Research)
Background Digital transformation is a key component within the National Health Service Maternity Transformation Programme. The COVID-19 pandemic led to an acceleration of digital innovation, in particular, the use of digital clinical consultations (telephone/video consultations). The ways in which digital clinical consultations can be optimised and utilised alongside the traditional maternity care pathway remains unclear, however, with particular concerns about the potential for digital care to exacerbate inequalities. Objective To explore how digital clinical consultations can be implemented in a clinically safe, appropriate and acceptable way within UK maternity services? For whom? In what settings? And for what purposes? Design A realist synthesis combining an evidence review of diverse sources (2010 to the present) from Organisation for Economic Co-operation and Development countries with insights from key stakeholder groups (healthcare professionals, service users and community organisations). Data sources There were three main sources: (1) published primary and secondary research; (2) grey literature (such as policy documents and maternity safety reports); and (3) stakeholder insights. Methods A realist synthesis adopts a theory-driven approach which seeks to understand how a complex programme works, for whom and under what circumstances. The review had three iterative phases: (1) refining the review focus and developing initial programme theories; (2) retrieval of evidence for data extraction and analysis (using on a realist logic to identify key contexts, mechanisms and outcomes); and (3) testing and refining the programme theories. Results The final synthesis included 93 evidence sources (reviews, reports and 77 primary studies), with priority given to UK-focused studies. Study samples included a focus on healthcare professionals (n = 17), women (n = 45, of which 14 focused on vulnerable groups) or both (n = 15). Clinical and safety-related outcomes were reported in 12 studies. Fifteen programme theories were developed. A conceptual framework was produced that illustrates the inter-relationship between key contexts in maternity care through which different interactions activate mechanisms to produce outcomes of interest. The findings suggest that digital clinical consultations can be acceptable and appropriate if implementation includes personalisation and informed choice for women, as well as support and autonomy for staff. The relationship and connection between women and their healthcare professional are proposed as key mechanisms that support safety and engagement in care. Limitations Some of the evidence lacked details regarding specific settings, interventions or sample characteristics. This limits the extent to which findings can be applied to micro-level contexts. Stakeholder groups contributed key insights to the review at all stages. In spite of efforts to achieve diversity within these groups, there may have been experiences or identities that were missed. Conclusions Four ‘CORE’ implementation principles were identified to guide future practice and research: C – Creating the right environment, infrastructure and support for staff; O – Optimising consultations to be responsive, flexible and personalised to different needs and preferences; R – Recognising the importance of access and inclusion; and E – Enabling quality and safety through relationship-focused connections. Future work Future research should embed equity considerations and should focus on understanding digital clinical consultation within specific maternity systems (like triage/helplines), services (such as specialist outpatient clinics) or groups of women (e.g. with digital literacy or communication needs). Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research as award number NIHR134535. Plain language summary What was the question? In recent years there has been a digital transformation in National Health Service maternity care, accelerated by the COVID-19 pandemic. To explore these changes in the delivery of care we asked: How can digital consultations (telephone and video calls) best be provided in maternity care? For whom are they appropriate? And what is needed to provide good quality care? What did we do? The research project involved three main phases. Phase 1 included discussions with groups of women and healthcare professionals as well as a brief review of existing academic research to identify key ideas (theories) on using digital consultations in maternity care. Phase 2 involved testing these theories by looking in-depth at more evidence. In phase 3, the quality and relevance of the evidence was assessed and more information gathered where necessary. The theories were then finalised and validated with stakeholders. This phase also included the development of recommendations for policy and practice. What did we find? The review highlighted 15 important considerations for providing digital consultations in maternity care. These were grouped into five main areas: (1) developing systems, facilities and resources; (2) training and communication; (3) access and inclusion; (4) personalisation and flexibility; and (5) quality of care. There is no-one-size-fits-all approach for delivering digital maternity care. It is important to give women and staff support to use digital processes and choice about the type of consultation that can best meet their needs. What does this mean? From the findings, four principles emerged for developing and using digital maternity consultations: Create an appropriate environment, structure and support for staff. For women, consultations need to be responsive and personalised to different needs and preferences. Services must recognise diverse circumstances and the importance of access and inclusion for all. Support a safe and high-quality service through building relationships.